2012
DOI: 10.1100/2012/750659
|View full text |Cite
|
Sign up to set email alerts
|

Is There an Association between Socioeconomic Status and Body Mass Index among Adolescents in Mauritius?

Abstract: There are no documented studies on socioeconomic status (SES) and body mass index (BMI) among Mauritian adolescents. This study aimed to determine the relationships between SES and BMI among adolescents with focus on diet quality and physical activity (PA) as mediating factors. Mauritian school adolescents (n = 200; 96 males, 104 females) were recruited using multistage sampling. Participants completed a self-reported questionnaire. Height and weight were measured and used to calculate BMI (categorised into un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 44 publications
(72 reference statements)
2
34
1
Order By: Relevance
“…Nonetheless, there was no indication that the relatively high prevalence of UW was associated with anaemia, as the prevalence of anaemia within the population was not noticeably elevated, and there was no observed relationship with BMI-for-age classification. Furthermore, in contrast to a recent small-scale study by Fokeena and Jeewon ( 24 ) , no relationship between BMI and socio-economic status (as measured by monthly family income) was observed, or any relation to diet type or daily fruit consumption.…”
Section: Discussioncontrasting
confidence: 99%
“…Nonetheless, there was no indication that the relatively high prevalence of UW was associated with anaemia, as the prevalence of anaemia within the population was not noticeably elevated, and there was no observed relationship with BMI-for-age classification. Furthermore, in contrast to a recent small-scale study by Fokeena and Jeewon ( 24 ) , no relationship between BMI and socio-economic status (as measured by monthly family income) was observed, or any relation to diet type or daily fruit consumption.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover Darmon et al 56 reported that adolescents with high SES had significantly higher percentage of energy intake from fat while the low SES had higher percentage of energy intake from carbohydrate. In contrast, Fokeena and Jeewon 42 reported that among Mauritian adolescents, consumption of vegetables, low fat protein sources, and sweetened and fatty foods were higher in the low SES group while the high SES group consumed more fruits, wholegrain cereals, refined cereals, milk and dairy products whether low fat or full-cream, and high fat protein sources along with fast foods. While high income people can afford healthy food products, adolescents with low SES do not always eat properly because of poverty 57 .…”
Section: Socioeconomic Status (Ses)mentioning
confidence: 91%
“…Socioeconomic status (SES) is postulated to be a major predictor of dietary intake and lifestyle which are the major contributors to weight problems 42 . In a study among Lebanese adolescents, energy and nutrient intake analysis showed that adolescents in the high-SES group consumed significantly higher amounts of calories, protein, fat and significantly lower amounts of carbohydrates 50 .…”
Section: Socioeconomic Status (Ses)mentioning
confidence: 99%
“…A meta-analysis of 43 studies of obesity and breast cancer revealed that obese patients were 33% more likely than non-obese patients to die of breast cancer (Protani et al 2010). Socioeconomic status has been classically known to impact on diet, with low level of education and moderate physical activity level, cost per calorie as important mediators identified in the socioeconomic status-BMI relationship (Dunneram and Jeewon 2013; Fokeena and Jeewon 2012). Previous trends have shown an increase in BMI and metabolic syndrome in the populations of higher socioeconomic strata among developing countries (Caballero 2007).…”
Section: Socioeconomic Impact Of Pops and Breast Cancermentioning
confidence: 99%